2008
DOI: 10.1177/193229680800200221
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pen—The “iPod” for Insulin Delivery (Why Pen Wins over Syringe)

Abstract: Diabetes affects most aspects of everyday life and places considerable responsibility on the patient; therefore, without patient acceptance of what we offer, the therapy is unlikely to be adhered to especially when that therapy happens to be insulin injection. In 2008, almost every physician/health care provider carries new and sleek cell phones (because the newer ones are well designed and function better). Why these same providers continue to prescribe insulin via syringes in 2008 is something that I cannot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“… 13 This finding was emphasized by Asamoah in his article titled “Insulin pen-the ‘iPod’ for insulin delivery (why pen wins over syringe)”. 14 An explanation of such cost saving is the possibility of less insulin wastage due to expiration with the insulin pen since one vial contains 1,000 units of insulin as compared of one box of 5 pens containing 1,500 units of insulin in total. 3 Another study, by Lee et al analyzed patients’ adherence and hypoglycemic incidents in patients who converted to pen use.…”
Section: Introductionmentioning
confidence: 99%
“… 13 This finding was emphasized by Asamoah in his article titled “Insulin pen-the ‘iPod’ for insulin delivery (why pen wins over syringe)”. 14 An explanation of such cost saving is the possibility of less insulin wastage due to expiration with the insulin pen since one vial contains 1,000 units of insulin as compared of one box of 5 pens containing 1,500 units of insulin in total. 3 Another study, by Lee et al analyzed patients’ adherence and hypoglycemic incidents in patients who converted to pen use.…”
Section: Introductionmentioning
confidence: 99%
“…7,23 Research demonstrates that convenience (or less lifestyle interference) is not only associated with increased satisfaction, but also with greater medication regimen adherence. 24 Another set of associations implicated affordability as an important factor in persistence of pen use. Patients who gave better ratings on the cost of pens and those with better insurance coverage (private or Medicare) were less likely to terminate their pen use.…”
Section: Discussionmentioning
confidence: 99%
“…7 In addition, they are very fine, short, and lubricated needles, reducing the painful bruising and bleeding that can be experienced with longer and thicker needles. 6 , 31 33 NovoTwist needles are designed to attach and detach NovoPen insulin devices using a twisting motion to increase the patient’s ease of use. 8…”
Section: Methods Of Insulin Delivery and Patient Usementioning
confidence: 99%
“… 2 Although it has been demonstrated that insulin pen devices are preferred by patients, vials and syringes are still widely used, even in industrialized countries such as the US. 6 …”
Section: Introductionmentioning
confidence: 99%